LungPoint - a new approach to peripheral lesions - Eberhardt, Ralf; Kahn, Nicolas; Gompelmann, Daniela; Schuhmann, Maren; Heußel, Claus Peter; Herth, Felix (Journal of thoracic oncology, 2010)
Introduction: - Although flexible bronchoscopy is the least invasive procedure for sampling, it is limited by its inability to reach lesions in the peripheral segments of the lung. Biopsy success is further compromised if the lesion is less than 30 mm in diameter or cannot be seen on fluoroscopy. We wanted to explore whether a new bronchoscopic navigation system could help access the peripheral lung airways and enable lesion sampling. - Methods: - The LungPoint system produced a virtual bronchoscopic pathway indicating the bronchus into which the bronchoscope should be advanced. Virtual bronchoscopic images were displayed alongside and registered with actual bronchoscopic video. After performing broncoscopy with a standard bronchoscope for first examination, the thin bronchoscope was advanced to the target bronchus under direct visualization without fluoroscopy. A pilot study included consecutive patients at a tertiary teaching hospital with pulmonary peripheral lesions (<42 mm). Biopsies were taken later. - Results: - Study subjects included 25 patients (9 women and 16 men, mean age 67 years) with 25 lesions (mean size 28 mm). Using this navigation system, the bronchoscope could be advanced along the planned route in all cases. In 14 of the cases (56%), the bronchoscope could be advanced all the way to the lesion bronchus. The planning time was a median of 5 minutes, and the median examination time was 15 minutes. A definitive diagnosis was possible in 20 cases (80%). One patient experienced a small pneumothorax because of the biopsy that resolved without drainage. No other complications occurred. - Conclusions: - This navigation system is useful for bronchoscopy for pulmonary peripheral lesions (NCT01067755).
Available online: 20 November 2015
Gesehen am 20.02.2023